Efficacy and Prognosis of Hyperbaric Oxygen as Adjuvant Therapy for Neonatal Hypoxic-Ischemic Encephalopathy: A Meta-Analysis Study - Gong, Xiu-Bing; Feng, Rui-Hua; Dong, Hong-Mei; Liu, Wen-Hua; Gu, Ya-Nan; Jiang, Xiang-Yue; Lou, Ye-Hao; Xu, Jun; Dou, Qing-Li (Frontiers in Pediatrics, 2022)
Background: Preclinical and clinical evidence suggests that hyperbaric oxygen therapy (HBOT) may benefit newborns. The effectiveness of HBOT for neonatal hypoxic-ischemic encephalopathy (HIE) remains controversial. We conducted a meta-analysis to evaluate the efficacy and prognosis of HBOT in neonates with HIE. Methods: A systematic search of eight databases was performed for available articles published between January 1, 2015, and September 30, 2020, to identify randomized controlled clinical trials (RCTs) on HBOT for neonatal HIE. Methodological quality assessment was performed by applying the simple procedure detailed by the Cochrane collaboration. Afterward, quality assessment and data analysis were performed using Revman 5.3 software. STATA 15 software was used to detect publication bias as well as for sensitivity analysis. Results: A total of 46 clinical RCTs were selected for the study and included 4199 patients with neonatal HIE. The results indicated that HBOT significantly improved the total efficiency (TEF) of treatment for neonatal HIE patients (odds ratio [OR] = 4.61, 95% confidence interval (CI) [3.70, 5.75], P<0.00001) and reduced the risk of sequelae (OR = 0.23, 95% CI [0.16, 0.33], P<0.00001) and the neonatal behavioral neurological assessment (NBNA) scores (mean difference [MD]=4.51, 95%CI [3.83,5.19, P<0.00001]). Conclusion: In light of the effectiveness of HBOT neonatal HIE, this meta-analysis suggested that HBOT can be a potential therapy for the treatment of neonatal HIE. Due to the heterogeneity of studies protocol and patient selection being only from China, more research is needed before this therapy can be widely implemented in the clinic.